Design Dashboard Model For Fish Processing System (Case Study PT Blue Ocean Grace International) - I Gede Sujana Eka Putra (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
The dashboard system is a graphical analytical model provided for management to present the information summary and quality of fish processing data in each stage processing in specific periods of time, from a company or an organization, the dashboard has been widely adopted by companies or businesses. The background of this research is a huge of complex processing data which is difficult and require sometimes to process and to present data analytical to management to monitor and review processing result and making decision based on data analytical. In this research, we design graphical analytical dashboard which make easy to present the quantity fish processed and seafood product summary analysis in each processing stage start from receiving, cutting, retouching, packing and shipment. By using this dashboard, management enable make quick decision based on analytical information related to how many fish processed, quantity of seafood product resulted per processing periods to decide and determining future plan strategy related to fish supply, market demand. The scope of this research is to present summary analytical data from the periods July until December of 2019. The dashboard model help management decision by presenting data analytical of fish processing.